Improvement of dielectrophoretic data analysis algorithm in determining the relative polarisability of dielectric particles / Robiyanti Adollah - Robiyanti, Adollah (2012)
In the past few years, there has been an extensive research in the manipulation and analysis of biological cells at the micro scale. DEP offer the ability to manipulate particles, especially living cells, is fundamental to many biological and medical applications, including isolation and detection of cancer cells, concentration of cells from dilute suspensions, separation of cells according to specific properties, and trapping and positioning of individual cells for characterization. The term DEP was first introduced by Pohl in 1951 to describe the transnational motion of particles due to the application of non-uniform electrical fields. The dielectrophoretic motion is determined by the magnitude and polarity of the charges induced in a particle by the applied field. DEP can be used to non-invasively determine electrophysiological parameters such as conductivity (defined as the ability to carry electrical charge) and permittivity (the ability to store electrical charge) of the cytoplasm and membrane of cells by monitoring the frequency-dependent DEP collection rate. Accurate determination of the DEP spectrum using simple image processing techniques by comparing the change in light intensity offer great possibility to study on polarisabality of cell for future used in integrated DEP system.